PORTUGUESE FOR FOREIGNERS: INTERFERENCE OF INTERLANGUAGE IN WRITING OF HISPANIC-AMERICAN STUDENTS: A CASE STUDY - Gomes Bastos, Francisco Glauco [UNESP]; De Lima, Jean Custdio [UNESP]; Arena, Dagoberto Buim [UNESP] (Univ Metodista Piracicaba-unimep, 2016)
This article deals with the interference of interlanguage in textual production of Hispanic-Americans students in learning Portuguese as a Foreign Language (PFL). These learners, subject of this work, although they have English as their official language in the US, where they live, they also have Spanish as the language of their parents, which is spoken at home by the whole family and with other countrymen due to the proximity of the state where they live (Arizona) to the Mexican border. Given the above, this research through a study case aims to analyze the written production by Errors Contrastive Analysis (ECA) in a class of Hispanic-American students who attend PLE intensively at the Federal University of Ceara (UFC). Finally, after so much research in the area, it is not certain whether there is the possibility to avoid totally fossilization process of interlanguages when learning a foreign language, however, we can make an effort, to raise awareness of students and teachers, by results obtained from research on the systematic errors found in the written productions, so that we can take interlanguage to levels closer and closer to a native writer.
Keywords: INTERLANGUAGE; FOSSILIZATION; ERRORS; WRITTEN PRODUCTION